Cerebral Hemodynamic Alterations in Dialysis COVID-19 Survivors: A Transcranial Doppler Ultrasound Study on Intracranial Pressure Dynamics - José Lapeña-Motilva; Daniel Fouz-Ruiz; Mariano Ruiz-Ortiz; Eduardo Sanpedro-Murillo; Sara Gómez-Enjuto; Inés Hernando-Jimenez; Aida Frias-González; Andrea Soledad Suso; Evangelina Merida-Herrero; Julián Benito-León (Kidney and Dialysis, 2025)
Background: We observed a COVID-19 survivor with a ventriculoperitoneal shunt who developed increased intracranial pressure during hemodialysis. We hypothesized that post-SARS-CoV-2 infection, patients may have altered cerebral perfusion pressure regulation in response to intracranial pressure changes. Methods: From April to July 2021, we recruited dialysis patients with prior COVID-19 from two Madrid nephrology departments. We also recruited age- and sex-matched dialysis patients without prior SARS-CoV-2 infection. Transcranial Doppler ultrasound was used to measure the middle cerebral artery velocity before dialysis and 30, 60, and 90 min after the initiation of dialysis. Results: The final sample included 37 patients (16 post-COVID-19 and 21 without). The COVID-19 survivors showed a significant pulsatility index increase between 30 and 60 min compared to those without COVID-19. They also had lower heart rates. Conclusions: We propose two mechanisms: an increase in intracranial pressure or a decreased arterial elasticity. A lower heart rate was also observed in the COVID-19 survivors. This study highlights SARS-CoV-2’s multifaceted effects, including potential long-term vascular and cerebral repercussions.